Telecommuting Application Opportunity in Indonesian Government (Peluang Pemanfaatan Telecommuting dalam Pemerintahan di Indonesia ) - Budhiekusuma, Noor Patria (Jurnal Pekommas, 2017)
The development of information technology and communication has reached standard significant influence in various fields, especially in an effort to reach competitive advantage. Mastery of ICT believed to increase productivity and efficiency in the organization/company, although some researchers make an exception in productivity paradox phenomenon. The development of ICT allow the the emergence of new innovations at the organization/company, one of which is telecommuting. Facilities and opportunities in telecommuting could be implemented under consideration internal organization/company. Opportunities to use telecommuting more broadly likely be applied in Indonesia especially in the field of government, of a wide geographical area as one consideration. Other consideration, governments implementation that always referred to regulations governing every aspect of government including information management. The Act of the Republic of Indonesia Number 14 of 2008 on Public Information Openness regulating the information service and openly by improving the quality of and keep secrecy information of being excluded. This research study against possible telecommuting in the implementation of governance in the country with regard to the quality of information and data of government according to the regulations apply. The conclusion of research is, telecommuting probable adopted in the implementation of governance in the country by right methods and appropriate regulations, to keep the purpose and dimension the quality of conforming parameter methodology the quality of information and data for the purpose the end was improving the quality of the information for the community.Perkembangan Teknologi Informasi dan Komunikasi telah mencapai taraf pengaruh yang signifikan di berbagai bidang, terutama dalam usaha mencapai keunggulan kompetitif. Penguasaan terhadap TIK diyakini meningkatkan produktivitas dan efisiensi dalam organisasi/perusahaan meski beberapa peneliti membantahnya dengan mengemukakan fenomena IT Productivity Paradox. Perkembangan TIK memungkinkan munculnya inovasi baru dalam organisasi/perusahaan, salah satunya adalah telecommuting. Fasilitas dan peluang dalam telecommuting dapat diimplementasikan berdasarkan pertimbangan internal organisasi/perusahaan. Peluang pemanfaatan telecommuting secara lebih luas kemungkinan dapat diterapkan di Indonesia khususnya dalam bidang pemerintahan, dengan cakupan wilayah geografis yang luas sebagai salah satu pertimbangan. Pertimbangan lain, pelaksanaan pemerintahan selalu mengacu pada regulasi yang mengatur setiap aspek pemerintahan termasuk pengelolaan informasi. Undang-Undang Nomor 14 tahun 2008 tentang Keterbukaan Informasi Publik mengatur pengelolaan dan pelayanan informasi secara terbuka dengan meningkatkan kualitas dan tetap menjaga kerahasiaan informasi yang dikecualikan. Penelitian ini melakukan kajian terhadap kemungkinan implementasi telecommuting dalam pemerintahan di Indonesia dengan memperhatikan faktor kualitas informasi dan data pemerintahan sesuai dengan regulasi yang berlaku. Kesimpulan dari penelitian ini adalah, telecommuting sangat mungkin diadopsi dalam pelaksanaan pemerintahan di Indonesia dengan metode yang tepat dan sesuai dengan regulasi, untuk menjaga tujuan dan dimensi kualitas sesuai parameter metodologi kualitas informasi dan data sehingga perbaikan kualitas layanan informasi untuk masyarakat dapat dilakukan.